Body condition indices are better surrogates for lean mass and water content than for body fat content in an insect. (14th June 2021) - Stahlschmidt, Z. R.; Chang, E.
Abstract: Ecologists and evolutionary biologists often use body condition indices (BCIs) to approximate an animal's energetic state, which is important because energy (typically, lipid) reserves influence an animal's investment into fitness‐related traits. A BCI's utility is typically assessed by examining its ability to predict standardized fat content (fat mass in fresh mass after correcting for body size) across a population. Less frequently, a BCI is assessed as a response variable by comparing its sensitivity to a particular treatment or factor (e.g. food availability or age) relative to that of standardized fat content. We assessed five common BCIs (or equivalent) with these two approaches in the wing‐dimorphic sand field cricket ( Gryllus firmus Scudder 1902). All of the BCI methods significantly predicted standardized fat content in both sexes and wing morphs where the scaled mass index and Que ́telet's index explained the most and least amount of variation, respectively. The BCIs and fat content were also similarly affected by adult age. However, BCIs were universally better proxies for lean mass and water content than for fat content. The relationships between BCIs and standardized lean mass and water content were stronger than those between BCIs and standardized fat content, and the effect sizes of age on BCIs were closer to that of lean mass relative to that of fat content. Thus, although BCIs reasonably predicted energy (fat) stores in G. firmus, they may be more indicative of lean mass or water content in insects. If BCIs are surrogates for protein and water storage, they may still approximate the storage of resources that fuel fitness‐related traits. Yet, future work is required to understand which body components (e.g. fat, protein or water) are most tightly linked to fitness, and whether traditional BCIs explain variation in fitness‐related body components across animal taxa. Abstract : Ecologists and evolutionary biologists regularly use body condition indices (BCIs) as proxies for animal energy (lipid) reserves, but the link between BCIs and fat content is often tenuous. In a field cricket, we show that common BCIs predict fat content, but they are stronger indicators of lean mass (a proxy for protein content) and water content than fat content.